2015
DOI: 10.5966/sctm.2014-0259
|View full text |Cite
|
Sign up to set email alerts
|

Postinfarction Functional Recovery Driven by a Three-Dimensional Engineered Fibrin Patch Composed of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells

Abstract: Considerable research has been dedicated to restoring myocardial cell slippage and limiting ventricular remodeling after myocardial infarction (MI). We examined the ability of a three-dimensional (3D) engineered fibrin patch filled with human umbilical cord blood-derived mesenchymal stem cells (UCBMSCs) to induce recovery of cardiac function after MI. The UCBMSCs were modified to coexpress luciferase and fluorescent protein reporters, mixed with fibrin, and applied as an adhesive, viable construct (fibrin-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 50 publications
(65 reference statements)
0
40
0
Order By: Relevance
“…In this context, due to their regenerative and immunomodulatory capacities, mesenchymal stem cells (MSCs) have been proposed as powerful inhibitors to counteract such unwanted immune responses. Thus, MSCs represent a promising strategy for a variety of medical conditions, including treatment of damaged tissue, inflammatory diseases and transplantation 1,2.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, due to their regenerative and immunomodulatory capacities, mesenchymal stem cells (MSCs) have been proposed as powerful inhibitors to counteract such unwanted immune responses. Thus, MSCs represent a promising strategy for a variety of medical conditions, including treatment of damaged tissue, inflammatory diseases and transplantation 1,2.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, when using cell types such as skeletal myoblasts, poor electrical integration into the host tissue can lead to secondary complications such as arrhythmias [19]. The use of tissue-engineered grafts has also shown significant promise in small animal models [2024], but concerns about cell/ graft viability and the level of cell maturity have limited the clinical potential of tissue-engineered grafts. Future success and development of cardiomyoplasty- and cardiac graft-based treatment strategies would benefit from optimized in vitro methods to evaluate cardiomyocyte (CM) viability, phenotype, maturation level, and contractility under varying conditions that mimic the in vivo cellular environment.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the MSCs from other tissues, hUCMSCs can give rise to different cell types including bone, cartilage, adipose tissue, cartilage, and neuron . Preclinical studies have revealed that transplantation of an engineered fibrin patch composed of hUCMSCs can improve cardiac function after myocardial infarction and the implanted cells contribute to the formation of new, functional microvasculature . Another study reported that transplantation of chitosan scaffolds seeded with hUCMSCs facilitates brain tissue regeneration in a rat model .…”
Section: Discussionmentioning
confidence: 99%